2021
DOI: 10.1002/eap.2443
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use change alters associations between personality and microhabitat selection

Abstract: Ecologists commonly assess ecological patterns at the population level, focusing on the average response of all individuals within a population, but to predict how populations will respond to land‐use change we must understand how changes to habitat differentially affect individuals within a population. For example, forest management is a widespread type of land‐use that impacts wildlife through the loss of key habitat features, but individuals within a population may vary in their responses to this loss due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 146 publications
3
19
0
Order By: Relevance
“…Our finding that individuals exhibiting boldness in the open‐field test were more likely to select for covered sites could evidence a competitive advantage of individuals willing to explore risky areas outcompeting more timid individuals for better foraging sites. These findings are in line with recent work in our study system, where it was found that bolder voles selected microhabitats with more food resources (Brehm & Mortelliti, 2021). Here, these individuals also had a higher probability of selecting high‐quality seeds, lending support for the idea that they may have increased competitive ability over more timid individuals.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our finding that individuals exhibiting boldness in the open‐field test were more likely to select for covered sites could evidence a competitive advantage of individuals willing to explore risky areas outcompeting more timid individuals for better foraging sites. These findings are in line with recent work in our study system, where it was found that bolder voles selected microhabitats with more food resources (Brehm & Mortelliti, 2021). Here, these individuals also had a higher probability of selecting high‐quality seeds, lending support for the idea that they may have increased competitive ability over more timid individuals.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we investigated these relationships, pursuing the following objectives: objective 1: determine whether personality predicts foraging site selection in southern red‐backed voles; objective 2: assess whether foraging decisions vary with personality and/or microsite selection; and objective 3: investigate whether personality and perceived risk interact to mediate foraging outcomes. Following previous findings showing that individual microhabitat use varies with personality (Bonnot et al, 2018; Schirmer et al, 2019), we predict that personality in southern red‐backed voles will mediate foraging site selection, specifically predicting that more active voles will select sheltered sites more often, in line with findings from Brehm and Mortelliti (2021) on vole microhabitat use. Additionally, it has been found that bolder voles select for areas with more food resources, potentially demonstrating a competitive advantage (Brehm & Mortelliti, 2021).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…At the same time, the magnitude and incidence of extreme weather events are expected to increase (IPCC, 2022), so species' persistence along an expanding high‐latitude range limit will also depend, in part, on the ability of individuals to contend with extreme, short‐term weather events (Early & Sax, 2011). As both land use and climate change interact to shape species' distributions through time (Brehm & Mortelliti, 2021; Saunders et al, 2022), identifying behavioral responses to bioclimatic variability as a function of landscape characteristics, and the resources they provide, can yield a more mechanistic understanding to predict future range shifts.…”
Section: Introductionmentioning
confidence: 99%